Formulation and evaluation of multiparticulate system for chronotherapeutic delivery of salbutamol sulphate - M Pallavi Chaudhari; D Pravin Chaudhari (Wolters Kluwer Medknow Publications, 2012)
Solution layering technique was used to prepare pellets of Salbutamol Sulphate. A multiparticulate system was prepared with pH independent and pH dependent coatings, and evaluated as pulsatile drug delivery system. Salbutamol sulphate release was studied from methacrylate coated pellets from non pareils. Morphology was studied using Scanning Electron Microscopy for the characterization of prepared pellets. Combination of Eudragit RSPO (pH independent) and Eudragit L100 (pH dependent) was used for coating of the pellets. Different concentrations of this polymeric combination were loaded on to the drug-loaded pellets. The aim of this study was to investigate the effect of physicochemical properties of the polymers on the release profile of Salbutamol sulphate from the pellets dosage form. The in-vitro study suggested that Eudragit RSPO and Eudragit L100 at 10% coating level led to an optimum pulsatile release behavior. The coated pellets prepared by solution layering technology successfully released drug after specific lag time indicating pulsatile drug delivery. It was revealed that Eudragit RSPO has the effect to retard drug release. The results generated in this study showed that proper selection of polymeric materials based on their physicochemical properties is important in designing pellets dosage form with suitable dissolution profile.